Attitude and Stance in Discourse - Ionescu-Ruxăndoiu, Liliana; Constantinescu, Mihaela-Viorica; Stoica, Gabriela; Hartular, Şerban (Cambridge Scholars Publisher, 2022)
Stancetaking is inherent in verbal communication, as it is connected with the expression of subjectivity and the construction of intersubjectivity in discourse. This book presents theoretical findings in this field and their practical implications, exploring the variations in time and space of meaning negotiation processes in a large variety of communicative forms, including political and judicial discourse, journalism, fiction, private letters, informal conversations, and school debates. Some articles refer to events with a strong impact on social and political life, such as the COVID-19 pand.